Vitamin D and Neurological Status in Sturge-Weber Syndrome. Issue 4 (29th September 2021) - Smegal, Lindsay F.; Lin, Doris D.; Cho, Andrew; Cho, Subin (Claire); Kalb, Luther G.; Cohen, Bernard; Germain-Lee, Emily L.; Comi, Anne M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: This study investigated the frequency of vitamin D deficiency (≤20 ng/mL) and insufficiency (21–29 ng/mL), as well as the relationship between vitamin D levels and neurologic function in Sturge-Weber syndrome (SWS). Methods: Fifty-eight subjects with confirmed SWS and at least one serum 25-hydroxyvitamin D level were studied. Prevalence of vitamin D deficiency and insufficiency were calculated. Nonparametric correlations analyzed relationships between vitamin D levels, neurological scores, and number of anticonvulsants. Demographics, SWS characteristics, MRI scores, and subject residence were considered. Results: Sixty-six percent of subjects had vitamin D levels below normal range. Abnormal levels occurred more frequently in Black or African Americans ( P = 0.041) and subjects with more severe brain involvement ( P = 0.027). Subjects with early seizure onset and bilateral brain involvement (n = 7) demonstrated greater improvements in hemiparesis with greater increases in vitamin D level (r = –0.791, P = 0.034). Subjects with greater than 3 lobes involved and early seizure onset showed larger improvements in hemiparesis with larger increases in vitamin D level (n = 10, r = –0.696, P = 0.025). Black or African Americans (n = 9) demonstrated greater improvements in total neurologic score (r = –0.865, P = 0.003) and hemiparesis (r = –0.697, P = 0.037) with greater increases in vitamin D level. Conclusion: Vitamin D deficiency and insufficiency are common in patients with SWS. Improvements in neurologic function may be seen with supplementation, especially in Black or African Americans as well as in severely affected patients, suggesting the utility of vitamin D as a therapeutic intervention. More research is needed to confirm and extend these findings.